Pre-simulator training as a joint bridge between theory and practice - Петращук, О.П.; Рудас, С.І. (Proceedings of National Aviation University (archive), 2010)
This article is about modern requirements for air traffic controllers’ qualification and its connection with the task to further to improve methods of their initial professional training. The improvement should be based on the latest approaches to provision of quality professional education.